PERAN GURU DALAM MEMBANGUN KARAKTER SISWA MELALUI PEMBIASAAN BUDAYA LITERASI DI SEKOLAH DASAR - Anggita Damayanti; Arifah; Risa Nurkomariyah; Nur Jamilah; Alif Rahmatullah; Moh Alfito Dwiky Denova (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education is a crucial element in the world of education that aims to shape students' personalities with moral values, ethics, responsibility, and good attitudes. Elementary schools function as an early environment that is very influential in shaping students' characters. Through the educational process, individuals can develop their potential, improve reading skills, and build a strong personality. This study aims to analyze the role of teachers in shaping students' characters and improving literacy culture. The method used in this study is a literature review, where the author refers to various sources from scientific journals and books that are relevant to the problems discussed. The results of this study indicate that character education is very important to be implemented in formal, informal, and non-formal education. One concrete example is the literacy culture taught to children from an early age. Through character education, it is hoped that children can grow into better individuals.